Russian Confessional Groups Today: Surroundings and Contacts with Other Confessions - Евгеньевна Никитина, Серафима (Slavistica Vilnensis, 2001)
The article examines the types of surroundings and contacts with other confessions experienced by three Russian confessional groups: the Old Believers, Dukhobors, and Molokans. These two issues are intrinsic parts of a comparative description of confessional cultures, and a number of parameters are introduced for each culture, for purposes of producing the description. The type of surroundings (horizontal and vertical) and kinds of contacts are the parameters of the category “confessional culture and the external world”. For the recent and contemporary state of confessional cultures, mention is made of the popular ecumenicism that occurs when there are no operating churches: Russian Orthodox congregants join with members of the Old Believers’ denominations which may be treated as a popular protestants, in order to conduct the necessary rites, in particular burials.